Factors Affecting Traffic Accidents on the Rajekwesi-Songgoriti Road Section, Batu City - Galih Damar Pandulu; Blima Oktaviastuti; Rifky Aldila Primasworo; Aprianus Sairo Lende (PT FORMOSA CENDEKIA GLOBAL, 2023)
Batu City is often used as a tourist destination city for the community, because it has beautiful nature and is surrounded by mountains and cool air which is one of its attractions. More tourists who visit are dominated by people outside Batu City, which results in higher transportation density. If this situation is not supported by good facilities or infrastructure in the field of traffic, it can have a major impact on traffic conditions. Traffic accidents that are very diverse, both in terms of the process of occurrence and the causal factors, often occur on the roads in Batu City. The purpose of this study is to determine the factors that cause accidents on the Rajekwesi road in Batu City. The research design used is a quantitative method with descriptive and survey research types. The data used are primary data and secondary data. The results of the study are based on accident data analysis for calculating the average accident equivalent number (AEK) of 53. Factors causing accidents which include human factors, vehicle factors, road factors, and environmental factors, indicate that Rajekwesi road, Batu City is classified as a vulnerable area accident. The need for additional road complementary facilities can be one of the efforts to reduce accidents on the Rajekwesi road, Batu City.